2016
DOI: 10.18632/oncotarget.11493
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of insulin-like growth factor II (IGF-II)-dependent cell growth by multidentate pentamannosyl 6-phosphate-based ligands targeting the mannose 6-phosphate/IGF-II receptor

Abstract: The mannose 6-phosphate/insulin-like growth factor II receptor (M6P/IGF2R) binds M6P-capped ligands and IGF-II at different binding sites within the ectodomain and mediates ligand internalization and trafficking to the lysosome. Multivalent M6P-based ligands can cross-bridge the M6P/IGF2R, which increases the rate of receptor internalization, permitting IGF-II binding as a passenger ligand and subsequent trafficking to the lysosome, where the IGF-II is degraded. This unique feature of the receptor may be explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 90 publications
0
13
0
Order By: Relevance
“…The CI-MPR is multi-functional, in that it binds proteins bearing the M6P recognition marker as well as the peptide hormone insulin-like growth factor (IGF)-II (hence it is also called IGF-IIR/CI-MPR) [36]. The IGF2R/ CI-MPR rapidly recycles between the cell surface membrane and intracellular membrane compartments, providing for the rapid uptake of both IGF-II and M6P-linked lysosomal enzymes [39]. Clinical studies infusing GAA to patients have demonstrated that GAA has a plasma elimination half-life of 2-3 h, so GAA was quickly taken up into cells (United Surgical Partners International and European Medicines Agency Summary of Product Characteristics, updated 04/02/2020) and was not present in circulation, similar to animal studies [40].…”
Section: Discussionmentioning
confidence: 99%
“…The CI-MPR is multi-functional, in that it binds proteins bearing the M6P recognition marker as well as the peptide hormone insulin-like growth factor (IGF)-II (hence it is also called IGF-IIR/CI-MPR) [36]. The IGF2R/ CI-MPR rapidly recycles between the cell surface membrane and intracellular membrane compartments, providing for the rapid uptake of both IGF-II and M6P-linked lysosomal enzymes [39]. Clinical studies infusing GAA to patients have demonstrated that GAA has a plasma elimination half-life of 2-3 h, so GAA was quickly taken up into cells (United Surgical Partners International and European Medicines Agency Summary of Product Characteristics, updated 04/02/2020) and was not present in circulation, similar to animal studies [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, in line with the understanding that protein localization can affect Tm 34,35 , a subset of known and predicted translocating proteins displayed significant Tm shifts during infection. Among these was the multifunctional receptor IGF2R, a protein involved in intracellular retrograde transport 87 . IGF2R was reported to support the replication of the gamma herpesvirus HHV-8 and the retrovirus HIV-1 88,89 , and our results also establish it as a pro-viral factor during HCMV infection.…”
Section: Prm Validation Igf2rmentioning
confidence: 99%
“…In virtue of this binding, IGF2 can be internalized by the IGF2R and degraded in the lysosome. These compounds have been found to be successful at reducing cell viability, IGF2 induced proliferation, and survival in vitro [148]. Another channel for reducing IGF2 bioavailability would be to disrupt the imprinting of IGF2 gene in such a way that neither paternal nor maternal IGF2 copy expresses IGF2.…”
Section: Igf2 Targeting In Cancer and Therapy Resistancementioning
confidence: 99%